Orientation in the diagnosis of intraocular neoplasia, through intraocular fine needle aspiration (IFNA) - Guimarães, T. (2019)
IFNA is a safe diagnostic technique that allows diagnostic of neoplastic and inflammatory processes of the eye1. In cats melanoma is common in the eye, skin and oral cavity2. In the eyep, local infiltration to systemic metastases may occur2. Being, the IFNA a method that assists in the diagnosis and therapeutics1,3,4,5. An european female cat, seven years old, was presented to consultation with brown patches of progressive growth in the right iris for four months. The pupillary light reflex, dazzle and menace response were present, and the ocular echography showed an area with iris thickening and with hyperechogenicity1. Due to clinical suspicion of iris melanoma, it was requested radiographic examination of the thorax, abdominal ultrasonography, hematological and biochemical blood analysis1,2, revealing no alterations. The IFNA was performed under general anesthesia introducing the a 26 gauge needle near the limbus and directed to the iris lesion with the bevel facing the surface of the mass3,4. The technique was performed without complications. The cytology using hematoxylin and eosin staining revealed moderate cellularity composed of rounded cells with moderate nuclear pleomorphism, bulky, pale cytoplasm1. The atypical round cells were suggestive of round cell amelanotic melanoma. Due to the cytological orientation, the enucleation of right eye was advised to the owner, which was declined.The diagnosis of ocular melanoma can be directed on clinical grounds and confirmed by anatomopathological exams2. IFNA is a practical, method in aiding the differentiation of neoplastic from non-neoplastic processes. It also helps guiding the surgical procedure and establishing prognosis1,3,4,5.